2018
DOI: 10.1007/s11721-018-0157-x
|View full text |Cite
|
Sign up to set email alerts
|

Informative and misinformative interactions in a school of fish

Abstract: It is generally accepted that, when moving in groups, animals process information to coordinate their motion. Recent studies have begun to apply rigorous methods based on Information Theory to quantify such distributed computation. Following this perspective, we use transfer entropy to quantify dynamic information flows locally in space and time across a school of fish during directional changes around a circular tank, i.e. U-turns. This analysis reveals peaks in information flows during collective U-turns and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(77 citation statements)
references
References 99 publications
2
75
0
Order By: Relevance
“…These conjectures have been formalized in the context of information dynamics [56], verifying the hypothesis that the collective memory within a swarm can be captured by active information storage, while the information cascades are captured by conditional transfer entropy [57,58]. This has been further verified for real biological groups, such as swarms of soldier crabs [59], schools of zebrafish responding to a robotic animal replica [60], pairs of bats [61], rummy-nose tetras (Hemigrammus rhodostomus) fish schools [62], and so on.…”
Section: Introductionmentioning
confidence: 73%
“…These conjectures have been formalized in the context of information dynamics [56], verifying the hypothesis that the collective memory within a swarm can be captured by active information storage, while the information cascades are captured by conditional transfer entropy [57,58]. This has been further verified for real biological groups, such as swarms of soldier crabs [59], schools of zebrafish responding to a robotic animal replica [60], pairs of bats [61], rummy-nose tetras (Hemigrammus rhodostomus) fish schools [62], and so on.…”
Section: Introductionmentioning
confidence: 73%
“…In particular, with regard to the subject of this study, it is conceivable that the interactions of two-and three-fish groups may be different [35,36]. Many researchers, therefore, have considered information transfer (or causal relationships) among individuals in small groups [37,38,39]. The (local) transfer entropy is the preferred measure to use in this case [40,41,42,43,44,45].…”
Section: Introductionmentioning
confidence: 99%
“…The (local) transfer entropy is the preferred measure to use in this case [40,41,42,43,44,45]. For example, Crosato et al [39] showed that the transfer of misinformation happens in five-fish school when the whole school changes direction. Other studies suggest that active information storage can predict the timing when nontrivial information transfer happens [46,47].…”
Section: Introductionmentioning
confidence: 99%
“…Collective behaviors of fishes or birds are typical examples used to illustrate emergence and belong to the canonic examples of complex systems. We only begin to understand how these flows structure the system, and what are the spatial patterns of information transfer within a flock for example: [Crosato et al, 2017] introduce first empirical results with transfer entropy for fishes and lay the methodological basis of this kind of studies. Similarly, [Lecheval et al, 2018] show that nonlinear interaction between fishes are essential for the propagation of information in the school during a collective U-turn.…”
Section: Informational Complexity and Emergencementioning
confidence: 99%